The Role of Avoidant Attachment and Anxious Attachment in Romantic Jealousy Among Young Adults in Long-Distance Relationships. - Tomasoa, Afia Rachel; Yogi Wulandari, Primatia (CV RIFAINSTITUT, 2024)
This study explores the role of adult attachment in romantic jealousy among young adults engaged in long-distance relationships. With 102 participants aged 20-25 in long-distance relationships, the research employed a qualitative method using questionnaires. The analysis results indicate that avoidant attachment is not significantly associated with romantic jealousy (significance value 0.232 < 0.05), whereas anxious attachment plays a significant role (significance value 0.000 < 0.05). Consequently, the findings suggest that avoidant attachment does not contribute to romantic jealousy, while anxious attachment is a significant factor in romantic jealousy among young adults in long-distance relationships.